The regulation of working time in the European Union : gender approach = La réglementation du temps de travail dans l'Union européenne : perspective selon le genre (Frankfurt am Main, 1999)
"This book deals with the regulation of working time in the European Union. Changes in the patterns of employment, the organisation of production and, above all, gender relations have rendered obsolete the classical paradigm of industrial revolution. The implications for the regulation of working time in the Member States are explored with reference to the EU directive on working time (1993), the development of collective bargaining, and the prohibition of indirect discrimination. This is all about equality between sexes in the matter of the use of time in the European society. Conference organized by the European Forum - European University Institute (Florence)."